eCorsi: implementation and testing of the Corsi block-tapping task for digital tablets - Brunetti, Riccardo; Del Gatto, Claudia; Delogu, Franco (Frontiers in Psychology, 2014)
The Corsi block-tapping task is a widely used test to assess visuo-spatial working memory. The test is traditionally administered using square blocks attached to a wooden board, but numerous digital versions have been developed. In this study we tested one-hundred and seven participants divided into two age groups (18-30 and over 50) in forward, backward and supraspan-forward conditions with eCorsi, a tablet version of the Corsi task. eCorsi, compared to the traditional physical board, presents a number of advantages, including: simple installation, set-up, and use; considerably increased accuracy in presentation timing, automatic measures of span and reaction times, in either forward or backward response modalities. Results showed that average span and error rates were essentially analogous to the ones obtained in the main standardization studies, which have used the original physical version of the Corsi test. In addition timing results provide new indications about the mechanisms underlying spatial sequence processing suggesting that the subject’s response is not planned during sequence presentation, but in the pause between the end of the presentation and the beginning of the response.